A new prediction method for the viscosity of the molten coal slag. Part 2: The viscosity model of crystalline slag. (15th May 2018) - Zhou, Jie; Shen, Zhongjie; Liang, Qinfeng; Xu, Jianliang; Liu, Haifeng
Highlights: A new method was used to calculate the relative viscosity of the molten slag. The viscosity prediction model of crystalline slag was obtained. The liquid phase viscosity was fitted by experiment data and FactSage respectively. Ten kinds of crystalline coals were used to verify the accuracy of the model. Abstract: The complex chemical composition of coal slag separated out different types and shapes of crystals during the cooling process. The morphology of the crystal in the molten slag influenced the viscosity of the coal slag. The aim of this paper was to obtain the viscosity model of crystalline slag using a new calculation method. The model of the suspension viscosity obtained by the previous study was used to predict the viscosity of molten slag. The correction factor ( β ) was introduced in the model of the suspension viscosity. The solid phase volume fraction ( φ ) in the molten slag was calculated by FactSage. The liquid phase viscosity ( η0 ) was fitted by the viscosities of molten slag in high temperature section. Ten kinds of crystalline slags were applied in this study to prove the accuracy of the modified viscosity model. The viscosity of molten slag predicted by the model (CSM) agreed with experiment data.